Additions to the angiosperm flora in the Sitapahar reserve forest of Kaptai, Rangamati, Bangladesh - Harun-Ur-Rashid, Mohammad; Chowdhury, Md. Aminul Islam (Bangladesh Journal of Plant Taxonomy, 2013)
Not available. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17401 Bangladesh J. Plant Taxon. 20(2): 255-257, 2013